Comparative Analysis of Phonetic Errors in Speech of Qolloquial in Arabic Song by Non Arabic Speakers - Andini Zahrotun Nisa; Mohamad Zaka Al Farisi; Hikmah Maulani; Zahra Auliya (Mantiqu Tayr: Journal of Arabic Language, 2024)
The Egyptian Qolloquial Arabic is widely used to articulate Arabic song lyrics, which have phonological differences that can alter the sounds of spoken words. These differences occur in specific phonemes, including the phonem [q] and [ʤ] changing to the phonemes [ʔ] and [ɣ]. This research employs a comparative qualitative method and document analysis through Pra at analysis to obtain visualization results of speech sound errors when pronouncing the phonemes [ʔ] and [ɣ]. Them form of speech sound errors in this study is obtained through a comparative analysis of the phoneme sounds of Native Speaker and Non Arabic Speakers. The data on speech errors were collected from four stanzas of Egyptian Qolloquial Arabic song lyrics. The results of this study show substitution errors of the phoneme [ʔ], which canges into the phoneme [ʕ]. Meanwhile, the pronounciation of the phoneme [ɣ] is articulated like the phonem [g] in Indonesian. This study also shows errors related to the addition and deletion of speech sounds at the beginning of words. These errors refer to the phonetic structure components, including the nature and articulation area of the phoneme, as well as the acoustic components in the fundamental frequency and sound intensity. This research is a novelty in Arabic linguistics by comparatively analyzing phoneme speech errors of Non Arabic Speakers when articulating  Arabic songs. Therefore, it is hoped that future research can develop studies that analyze vocal speech errors in using Egyptian Qolloquial Arabic when articulating other Arabic songs.